2010
DOI: 10.1111/j.1471-4159.2010.06877.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GABA‐B receptors induced by systemic amphetamine abolishes dopamine release in the rat lateral septum

Abstract: The lateral septum is a brain nucleus involved in various mental disorders such as anxiety and drug addiction. In the present study, we investigated whether systemic amphetamine, known to release dopamine (DA) in nucleus accumbens, will also release DA in lateral septum. Our results show that systemic amphetamine administration (2 mg/kg i.p.) induced a significant increase in DA extracellular levels in nucleus accumbens but not in lateral septum. Interestingly, intralateral septum perfusion of amphetamine thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…HPLC‐Electrochemical determination of DA was performed as described previously . Briefly, 10 μL of dialysates was injected into an HPLC system with the following configuration: an isocratic pump (model PU‐2080 Plus, Jasco Co. Ltd., Tokyo, Japan), a UniJet microbore column (MF‐8949, BAS, West Lafayette, IN, USA) and an amperometric detector set at 650 mV and 0.5 nA (model LC‐4C, BAS).…”
Section: Methodsmentioning
confidence: 99%
“…HPLC‐Electrochemical determination of DA was performed as described previously . Briefly, 10 μL of dialysates was injected into an HPLC system with the following configuration: an isocratic pump (model PU‐2080 Plus, Jasco Co. Ltd., Tokyo, Japan), a UniJet microbore column (MF‐8949, BAS, West Lafayette, IN, USA) and an amperometric detector set at 650 mV and 0.5 nA (model LC‐4C, BAS).…”
Section: Methodsmentioning
confidence: 99%
“…ADHD medication increases GABA in animal models (Freese et al, 2012, Goitia et al, 2013, Sotomayor-Zárate et al, 2010) and Bollmann et al (Bollmann et al, 2015) have demonstrated that age is a factor that needs to be considered as the GABAergic system continues to develop throughout childhood and adolescence (Andersen, 2003, Luján et al, 2005). Hence, an aberration from the normal development of the GABAergic system could result in a later imbalance between excitatory and inhibitory neurotransmission, that could play a role in the pathophysiology and persistence of ADHD (Ferreira et al, 2009, Luján et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the differential effect of AMPH over K + ‐induced dopamine release in different brain regions could be due to region‐specific effects of AMPH depending on other AMPH‐sensitive neurotransmitter systems. For instance, acute systemic administration of AMPH does not increase LS DA extracellular levels but readily increases NAcc DA extracellular levels of the same animals (Sotomayor‐Zarate et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our laboratory group showed that acute systemic administration of morphine increases DA extracellular levels in the rat LS (Sotomayor et al, ). However, we have shown that acute systemic amphetamine (AMPH) administration does not induce an increase in DA extracellular levels in the LS (Sotomayor‐Zarate et al, ). In addition, we reported that direct intra LS infusion of AMPH increases LS DA extracellular levels and that the lack of effect with systemic AMPH depends on the activation of LS GABA B receptors.…”
mentioning
confidence: 99%